The Ideas of Love in William Shakespeare’s Sonnets: An Existential-Psychological Analysis Based on Rollo May’s Theory of Love - Agra Liz Tantri; Fatimah Muhajir (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This study aims to examine the representation of the idea of love in three famous sonnets by William Shakespeare: Sonnet 18 (“Shall I compare thee to a summer’s day?”), Sonnet 116 (“Let me not to the marriage of true minds”), and Sonnet 64 (“When I have seen by Time’s fallen hand defaced”), written during the Renaissance period. Using a humanistic approach, this study seeks to uncover how Shakespeare portrays love as a human experience using Rollo May's existential theory of love, which encompasses four forms of love: Sex, Eros, Philia, and Agape. The approach used was qualitative-descriptive, with textual analysis of lines of sonnets containing the theme of love. The focus of the research was to identify how Rollo May’s forms of love can be found and interpreted in those sonnets. The results show that the three sonnets do not emphasize the physical aspect of love (sex), but rather present a deeper and more complex form of love. The findings demonstrate that love in Shakespeare's sonnets has an existential dimension that aligns with Rollo May's view of love as a profound and meaningful human experience.